Boy with dove, Frere temple - Ghosh, Ayan (2023)
The central allegorical figure of - Charity, grasping a sword (symbol of justice) with her right hand and sheltering a young boy holding a dove (symbol of peace). The figure is in a seated position with her head tilted towards the left.